Influence of Posterior Corneal Asphericity on Refractive Error of SRK-T and Barrett Formulas for Lucidis IOL - Rabinovich, Mark; Aramburu Del Boz, Ana Maria; Al-Khatib, Daniel; Genestier, Jean Pascal; Bovet, Jerome (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To evaluate the influence of posterior corneal asphericity on the refractive error using SRK-T and Barrett formulas for the intraocular lens (IOL) power calculation for Lucidis Extended Depth of Focus (EDOF) IOL.Setting This study was carried out at a tertiary ophthalmology center in Geneva, Switzerland.Design A retrospective study. Medical records from all enrolled patients were analyzed and the following information was extracted retrospectively, over 1 month following surgery.Methods We retrospectively reviewed 75 eyes that underwent cataract surgery and were implanted with a Lucidis EDOF IOL. We measured the posterior corneal asphericity (Q value), axial length (AL), and anterior chamber depth (ACD) and then calculated the IOL power using SRK-T and Barrett formulas.Results Seventy-five eyes were included, all of which had 1-month postoperative data. In the cohort, 32 eyes were from females (43%) and 43 from males (57%). The mean age of the study population was 73 ± 8.8 years. The mean AL was 23.5 ± 0.98 and the mean ACD was 3.13 ± 0.3. The mean posterior Q value was − 0.35 ± 0.2. In a regression analysis, we found a statistically significant relationship between the error in refraction prediction and the posterior Q value, irrespective of the formula used. The relationship between posterior corneal asphericity and the refraction prediction error was stronger for the Barrett II Universal formula than for the SRK-T formula.Conclusions Posterior corneal asphericity was correlated with the refractive error of calculation of both SRK-T and Barrett formulas, with a stronger correlation to the latter formula.
Keywords: cornea; asphericity; Lucidis; cataract; IOL; EDOF; SRK-T; Q value; Barrett; corneal asphericity